2018
DOI: 10.3390/f10010006
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Fusarium Root Rot and Development of Coastal Pine (Pinus thunbergii Parl.) Seedlings in a Container Nursery by Use of Bacillus licheniformis MH48

Abstract: This study investigated the control of Fusarium root rot and development of coastal pine (Pinus thunbergii) seedlings in a container nursery by using Bacillus licheniformis MH48. High-quality seedlings without infectious diseases cause vigorous growth. Fusarium root rot caused by Fusarium oxysporum is responsible for serious damage to coastal pine seedlings in nurseries. B. licheniformis MH48 produced enzymes that degraded the fungal cell walls, such as chitinase and β-1,3-glucanase. These lytic enzymes exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…Cell wall-degrading enzymes such as chitinase produced by antagonistic bacteria are known to play key roles in the suppression of phytopathogenic fungi [25][26][27][28][29][30]. In the present study, results of quantitative chitinase assay indicated that strain HS124 produced high levels of chitinase in colloidal containing medium (Figure 3).…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Cell wall-degrading enzymes such as chitinase produced by antagonistic bacteria are known to play key roles in the suppression of phytopathogenic fungi [25][26][27][28][29][30]. In the present study, results of quantitative chitinase assay indicated that strain HS124 produced high levels of chitinase in colloidal containing medium (Figure 3).…”
Section: Discussionsupporting
confidence: 52%
“…The experiment was repeated three times with three replications. The inhibition of fungal growth by the HS124 strain was determined with the following formula: inhibition (%) = [(α − β)/α] × 100, where α was the radial growth of phytopathogenic fungus on the control plate and β was the radial growth of phytopathogenic fungus on the dual culture plate [27,28,30].…”
Section: Antifungal Activity Of L Antibioticus Hs124 Toward Fungal Pmentioning
confidence: 99%
See 3 more Smart Citations